Morphological Description and Clinical Implication of Sphenopalatine Foramen for Accurate Transnasal Sphenopalatine Ganglion Block: An Anatomical Study - Sir, Ender (Medeni Med J, 2019)
OBJECTIVE: Transnasal sphenopalatine ganglion block is a commonly used approach for treatment of a variety of headache disorders. However, no standard technique has yet been defined for this less invasive approach. In this study, our aim was to investigate morphometric and anatomical features of the sphenopalatine foramen, and to describe a more efficient approach for transnasal sphenopalatine ganglion block. METHOD: The present study was designed retrospectively. Ten cadaver semi- heads and 18 adult dry skulls (28 samples totally) were included in the study. The distances between the sphenopalatine foramen and palatum durum, and also between the sphenopalatine foramen and the spina nasalis anterior, angle of elevation of the sphenopalatine foramen from palatum durum, and the length and width of the sphenopalatine foramen were measured. RESULTS: The mean width and length of the foramen were 3.79±0.35 and 6.44±0.94 mm, respectively. The mean distance between the palatum durum and the sphenopalatine foramen was 15.58±1.68 mm. The mean angle of elevation of the sphenopalatine foramen from the palatum durum was 26.10±3.97 degrees. The mean distance between the sphenopalatine foramen and the anterior nasal spine was 52.90±2.98 mm. CONCLUSIONS: In the transnasal sphenopalatine block, we suggest advancement of nasal applicator through superolateral direction for approximately 5.3 cm, and at an angle of about 26° from the nasal base..